Fading evolutions in multidimensional spaces - Pogorui A. О. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study fading random evolutions in multidimensional spaces. By reducing multidimensional cases to the one-dimensional case, we calculate the limit distributions of fading evolutions for some semi-Markov media.